Length of stay and associated factors in patients with schizophrenia and schizoaffective disorder in a specialised psychiatric hospital - Goga, Ladawa Yasese (My University, 2021)
Background: Patients with schizophrenia and schizoaffective disorder often require long admissions. There exists a progressive shortage of beds in South African psychiatric hospitals and investigating current length of stay (LOS) trends is necessary to better inform future health system planning. Aim: To explore LOS and associated factors of patients with schizophrenia and schizoaffective disorder, at a public sector specialised psychiatric hospital, over a 4- year period. Setting: The study was conducted at Tara Hospital, in Johannesburg, South Africa. Methods: A retrospective record review of 367 adult schizophrenia and schizoaffective disorder patients was conducted. Average LOS was calculated and the proportion of short-stay (<30 days), medium-stay (31-90 days) and long-stay (>90 days) admissions determined. Further data was collected, from a randomly selected subset of patients in each LOS category, regarding sociodemographic, clinical and admission outcome factors. Results: Mean LOS was 128 days (median 87, IQR 49-164, range 0-755 days). A significantly greater proportion of patients had long-stay admissions (p<0.001). Male gender (p=0.018), being unmarried (p=0.006), treatment resistant (p<0.001) and on clozapine (p=0.009) were factors found to have a significant association with long-stay admissions. Overall, rates of unemployment (>80%), comorbid substance use disorders (>40%), medical illnesses (>40%), antipsychotic polypharmacy (>40%) and readmissions (>80%) were high. Of those with treatment resistance, approximately half were discharged on clozapine. Most (>80%) were discharged home, despite psychiatric residential placement being recommended. Conclusion: Long-stay admissions were frequently required for patients with schizophrenia and schizoaffective disorder admitted to Tara Hospital. More research is needed into whether increased and improved community-based services such as residential and day-care facilities could translate into shorter admissions, less frequent relapses and improved outcomes in this population
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Psychiatry, 2021